2022
DOI: 10.3389/fonc.2022.831438
|View full text |Cite
|
Sign up to set email alerts
|

NCAPG as a Novel Prognostic Biomarker in Glioma

Abstract: BackgroundNon-SMC condensin I complex subunit G (NCAPG) is expressed in various human cancers, including gliomas. However, its biological function in glioma remains unclear. The present study was designed to determine the biological functions of NCAPG in glioma and to evaluate the association of NCAPG expression with glioma progression.MethodsClinical data on patients with glioma were obtained from The Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA), the Gene Expression Omnibus (GEO), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Immunotherapy plays an increasingly important role in standard cancer treatment, as it can recruit tumor-infiltrating T cells to eradicate tumor cells. In glioma, tumor-infiltrating CD4+ T cells play an important role in immune regulation [ 25 , 26 ]. GSEA showed that RPL4P4 expression was significantly involved in immune signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy plays an increasingly important role in standard cancer treatment, as it can recruit tumor-infiltrating T cells to eradicate tumor cells. In glioma, tumor-infiltrating CD4+ T cells play an important role in immune regulation [ 25 , 26 ]. GSEA showed that RPL4P4 expression was significantly involved in immune signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies have shown that the subunits of condensin, such as NCAPG, SMC4, and NCAPG2, have been reported to be involved in the glioma pathogenesis. Wherein, NCAPG could be positively related to CDCA2 (cell division cycle-associated protein 2) in glioma, and the over-expression of NCAPG may regulate the cell cycle and promote the proliferation, migration, and invasion of glioma cells (Liang et al, 2016 ; Jiang et al, 2022 ; Jin et al, 2022 ). Meanwhile, NCAPG overexpression can also increase the expression of MHCI and AMAD17 molecules, both of which are located on the tumor surface, thus, assisting in camouflaging the tumor and preventing NK cells from being activated in the immune microenvironment (Zheng et al, 2022 ).…”
Section: Condensin and Nervous System Tumorsmentioning
confidence: 99%
“…The malignant tumor patient prognosis is still poor [ 2 ]. In recent years, the number of tumor patients is gradually increasing, and the effectiveness of treatment is not ideal [ 3 ]. Therefore, the development of effective and specific tumor markers is extremely urgent for the diagnosis and treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%